Effects of heat stress and exposure duration on survival characteristics of different developmental stages of Propylaea japonica, a dominant aphidophagous ladybeetle in China. (April 2020) - Pumhan, Netnapa; Tian, Mi; Xu, Li-Li; Jiang, Jun; Liu, Tong-Xian; Zhang, Shi-Ze
Abstract: Extreme high temperatures in summer become more and more universal. However, the effects of high temperature on fitness and performance of different developmental stages in most biological control agents are very limited. The purpose of this work was to evaluate the effects of heat stress and exposure duration on the survival characteristics of immature and adult stages of Propylaea japonica, a dominant aphidophagous ladybeetle in China. Here, we investigated the survival characteristics of different developmental stages in P. japonica when subjecting to high temperatures, 35, 37, 39, 41 and 43 °C for exposure durations of 1, 2, 4 and 6 h, respectively, and 25 °C is the control. The results indicated that egg survival greatly decreased only at 43 °C for 4 h or 6 h, and had no significant difference from 25 to 41 °C for any exposure duration. The younger larvae were the most vulnerable stage with the minimum survival exposure to high temperature but older larvae showed stronger resistance to heat stress. The survivals of pupae and adult stages rapidly decreased only at 43 °C for exceeding 2 h. These results suggest that different developmental stages of P. japonica possess different degrees of heat resistance, which ensures its survival in summer. Moreover, according to the heat resistance of several natural enemy insects in our previous reports and the present results, a comprehensive utilization strategy of aphid biological control was constructed to restrain aphid damage and population growth in challenging environment. Highlights: The heat tolerances of different developmental stages of P. japonica were explored. The egg was the most resistant to heat stress. The first instar larvae were the most sensitive to heat stress. The female exhibited more resistant to high temperature stress than male. The integrated application strategy of aphid biological control was constructed.